2014
DOI: 10.1371/journal.pbio.1001833
|View full text |Cite
|
Sign up to set email alerts
|

CD4CD8αα Lymphocytes, A Novel Human Regulatory T Cell Subset Induced by Colonic Bacteria and Deficient in Patients with Inflammatory Bowel Disease

Abstract: Gut bacterium Faecalibacterium prausnitzii activates a newly identified set of human IL-10-producing Treg cells (CD4CD8αα lymphocytes), revealing a mechanism by which commensal microbes contribute to host immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 40 publications
(74 reference statements)
5
104
1
1
Order By: Relevance
“…38,39 This may be partly explained by the important role of gut bacteria in the induction of colonic regulatory T cells (T regs ). 40,41 A recent elegantly designed murine study reported that the reduction in the microbiota-derived short-chain fatty acids, specifically the histone deacetylase inhibitor (HDACi) butyrate, in intestinal epithelial cells was associated with GVHD. 42 In this study, restoration of butyrate improved intestinal epithelial junctional integrity, decreased apoptosis, decreased clinical GVHD scores and improved survival.…”
Section: Recovery Of Mucosal Injurymentioning
confidence: 99%
“…38,39 This may be partly explained by the important role of gut bacteria in the induction of colonic regulatory T cells (T regs ). 40,41 A recent elegantly designed murine study reported that the reduction in the microbiota-derived short-chain fatty acids, specifically the histone deacetylase inhibitor (HDACi) butyrate, in intestinal epithelial cells was associated with GVHD. 42 In this study, restoration of butyrate improved intestinal epithelial junctional integrity, decreased apoptosis, decreased clinical GVHD scores and improved survival.…”
Section: Recovery Of Mucosal Injurymentioning
confidence: 99%
“…Interestingly the Metastats defined the genus Clostridium_IV more abundant in the Landrace. The genus Clostridium_IV was previously reported to play a key role in systemic immunity (Sarrabayrouse et al, 2014). The less opportunistic pathogens identified in the Landrace could be due to the existence of the prevalent Clostridium species, however further studies are needed to confirm this.…”
Section: Genus Level Differential Abundance Testmentioning
confidence: 92%
“…Moreover, it is able to stimulate a recently identified human regulatory T cell subset (CD4CD8αα) [61]. These data pave the way to use anti-inflammatory commensals or their active metabolites as treatment for IBD.…”
Section: New Generation Of Probiotic Strains or Combinationsmentioning
confidence: 99%